Efforts To Increase Children's Interest In Learning And Spiritual Attitudes And Build Community Awareness On Environmental Sustainability In Manunggal Village - Dini Arianti (Journal of Community Service For Indonesian Society, 2023)
Education is very important today, especially moral development. Problems often occur in social life. Especially social issues. This research focuses on social problems, namely education, spiritual attitudes, and the environment which are difficult to solve if there is no awareness, interest, and enthusiasm from within each individual. Education has become a necessity for everyone, especially for those with high aspirations. Education is all-encompassing, as well as its impact on life. For this reason, this research was conducted which aims to increase children's interest in learning, instill spiritual values ​​in children, and build public awareness of environmental sustainability. This study uses a qualitative method by using direct interviews with several parties concerned about the problems being experienced in Manunggal Village. The subjects used were children and the surrounding community related to where the research was conducted. Data was collected by conducting interviews, analysis, and observation. The results showed that there was an increase between scores before attending tutoring and after attending tutoring due to an increase in interest in learning based on pre-study results which showed that not all children showed improvement, but these children gave their best efforts even though the results were not optimal, there were changes. children's attitudes and ways of thinking about religion and decency.